The Impact of Credit Access on Economic Growth in SEA Countries - Idroes, Ghalieb Mutig; Maulidar, Putri; Marsellindo, Rio; Afjal, Mohd; Hardi, Irsan (Indatu Journal of Management and Accounting, 2024)
Access to credit serves as a vital catalyst for economic growth, allowing individuals, enterprises, and governments to fund investments, maintain consumption stability, and encourage productive endeavors. Economic growth is fundamental to sustainable development, enhancing living standards, and promoting innovation. This study investigates the impact of credit access on economic growth in Southeast Asia (SEA) countries using monthly data from 2014 to 2020. By applying the Fully Modified Ordinary Least Squares (FMOLS) method, along with robustness checks using the Dynamic Ordinary Least Squares (DOLS) technique, this study includes essential control variables such as capital, labor, and technology. The results reveal that credit access has a positive impact on economic growth, while capital and technology also contribute positively to economic growth. Conversely, labor shows a negative impact on economic growth within the region. These results are consistent across both the FMOLS and DOLS analyses. Based on these findings, Southeast Asian policymakers ought to facilitate credit accessibility by making loan applications more straightforward, minimizing bureaucratic obstacles, and providing lower interest rates, especially for small enterprises and marginalized communities. Moreover, encouraging financial institutions to lend more liberally and utilizing digital platforms can expand access. Additionally, investing in technology, improving capital formation, and tackling labor market challenges will more effectively align with the region's growth path.